No association between month of birth and biliary atresia in a country with tropical climate - Pornthep Tanpowpong (2019)
© 2018 Paediatrics and Child Health Division (The Royal Australasian College of Physicians) Aim: Children with biliary atresia (BA) born in countries with temperate climate showed month-of-birth (MoB) predilection during cooler months. To date, no study on the MoB–BA association has been performed in a tropical country. Our aim was to define MoB variation in children with BA in a tropical country. Methods: We studied 150 children diagnosed with BA between January 1996 and April 2015 at a teaching hospital. MoB was defined by two categories based on the precipitation: rain and dry, and three categories based on the air temperature: high, average and low. We applied the country's population data on the number of births in each period as the expected proportions of birth. Results: A slightly higher proportion of BA children was born in the rainy months (52.7%); however, the difference was not significant compared to the general population's birth (P = 0.87). For the MoB based on the air temperature, no statistically significant difference was noted. Males with BA seemed to have a greater MoB variation compared to females, but this did not reach statistical significance. Conclusion: We could not find an association between MoB and BA in a tropical country. Multinational studies may aid in understanding the MoB–BA association in the tropical countries.